Literary Version of the Relationship between Elizabeth I and Mary Stuart - Kápičková, Lucie (Univerzita Pardubice, 2023)
This bachelor thesis aims to analyse the relationship between the Queen of England, Elizabeth I and Mary Stuart, Queen of Scots, displayed in contemporary female writing. It provides a theoretical background of writing and publishing conditions for Scottish women writers in the late twentieth century, examines the rivalry between Scotland and England in the sixteenth century, explores the causes of a problematic relationship between Elizabeth I and Mary Stuart and observes the trial and the execution of Mary Stuart, Queen of Scots. Each chapter analyses its interpretation in the contemporary play Mary Queen of Scots Got Her Head Chopped Off by the Scottish author Liz Lochhead.
Literární verze vztahu Alžběty I. a Marie Stuartovny
Keywords: Marie Stuartovna; Alžběta I.; národní identita; moderní skotské spisovatelky; Mary Stuart; Elizabeth I; national identity; contemporary Scottish women writers